Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu Hamil Terhadap Pemanfaatan Buku KIA Di Puskesmas Majalengka - Idaningsih, Ayu; Khodijah, Upus Piatun; Latari, Ade Ira; Insani, Wulan Nur (Yayasan Jompa Research and Development, 2025)
The KIA book is a book that aims to improve the quality of MCH services so that it can reduce MMR and IMR. The importance of pregnant women's knowledge in using the KIA book is for early detection if they experience complications or danger signs during pregnancy. One of the factors that influences pregnant women's knowledge is health education. Objective: This research aims to determine the effect of health education on pregnant women's knowledge about the use of Maternal and Child Health (KIA) books. Method: This research used a pre-experimental research design in the form of one group pretest posttest, involving 21 research samples, the sampling technique used purposive sampling. Data collection uses knowledge questionnaires and SAP. Data analysis used frequency distribution and paired t-test. Results: The average knowledge of pregnant women about the use of MCH books before health education was 11.19. The average knowledge of pregnant women about the use of MCH books after health education is 17.71. The p value = 0.000 < α value = 0.05, thus Ho is rejected. Conclusion: There is an influence of health education on pregnant women's knowledge about the use of KIA books at the UPTD of the Majalengka Health Center, Majalengka Regency. Suggestion: Health workers should help pregnant women understand the MCH book, such as body changes, pregnancy problems, and the care needed during pregnancy and postpartum, which ultimately contributes to improving maternal health.